Advance care planning before and during the COVID-19 pandemic: an observational cohort study of 73 675 patients’ records - Philippa G McFarlane; Catey Bunce; Katherine E Sleeman; Martina Orlovic; Jonathan Koffman; John Rosling; Alastair Bearne; Margaret Powell; Julia Riley; Joanne Droney (BJGP Open)
Background: Advance care planning (ACP) was encouraged by policymakers throughout the COVID-19 pandemic. Little is known about use of ACP during this time. Aim: To compare use of ACP before and during the COVID-19 pandemic. Design & setting: Retrospective, observational cohort study comparing the creation, use, and content of Electronic Palliative Care Coordination System (EPaCCS) records in London. Individuals aged ≥18 years with a Coordinate My Care record, created and published in the pre-pandemic period (1 January 2018–31 December 2019), wave 1 (W1; 20 March 2020–4 July 2020), interwave (IW; 5 July 2020–30 September 2020), and wave 2 (W2; 1 October 2020–5 March 2021). Method: Patient demographics and components of ACP were compared using descriptive and comparative statistics. Results: In total, 73 675 records were included; 35 108 pre-pandemic, 21 235 W1, 6323 IW, and 9925 W2 (n = 1084 records not stratified as created and published in different periods). Most records were created in primary care (55.6% pre-pandemic, 75.5% W1, and 47.7% W2). Compared with the pre-pandemic period, the average weekly number of records created increased by 296.9% W1 (P<0.005), 35.1% IW, and 29.1% W2 (P<0.005). Patients with records created during the pandemic were younger (60.8% aged ≥80 years W1, 57.5% IW, 59.3% W2, 64.9% pre-pandemic [P<0.005]). Patients with records created in W1 had longer estimated prognoses at record creation (73.3% had an estimated prognosis of ≥1 year W1 versus 53.3% pre-pandemic [P<0.005]) and were more likely to be 'for resuscitation' (38.2% W1 versus 29.8% pre-pandemic [P<0.005]). Conclusion: During the COVID-19 pandemic increased ACP activity was observed, especially in primary care, for younger people and those not imminently dying. Further research is needed to identify training and planning requirements as well as organisational and system changes to support sustained high-quality ACP within primary care.